ANALYSIS OF DOWNTIME IN A TYPICAL NIGERIAN MULTINATIONAL BOTTLING COMPANY - ABAFI JOEL (Journal of Engineering Studies and Research, 2020)
Failure data were extracted from the report book of the case study company. These data were stratified and analysed.Data stratification was pivotal in the separation of failure data into smaller and more defined form based on a predetermined set of criteria. Filler system was found to have the highest percentage failure occurrences; hence a standby filler system became the best option. The study concluded that, although in a production/manufacturing system, downtime is inevitable but it can be limited to the planned downtime with respect to the typical Nigerian multinational bottling company.